Macroprudential policy: Case study from a tabletop exercise - Tobias Adrian; Patrick de Fontnouvelle; Emily Yang; Andrei Zlate (Federal Reserve Bank of New York, 2015)
Since the global financial crisis of 2007-09, policy makers and academics around the world have advocated the use of prudential tools for macroprudential purposes. This paper presents a macroprudential tabletop exercise that was aimed at confronting Federal Reserve Bank Presidents with a plausible, albeit hypothetical, macro-financial scenario that would lend itself to macroprudential considerations. In the tabletop exercise, the primary macroprudential objective was to reduce the likelihood and severity of possible future financial disruptions associated with the unwinding of the hypothetical overheating scenario. The scenario provided a path for key macroeconomic and financial variables that were assumed to be observed through 2016:Q4, as well as the corresponding hypothetical projections for the interval from 2017:Q1 to 2018:Q4. Prudential tools under consideration included capital-based tools such as the leverage ratios, countercyclical capital buffer, and sectoral capital requirements; liquidity-based tools such as the liquidity coverage and net stable funding ratios; credit-based tools such as caps on loan-to-value ratios and margins; capital and liquidity stress testing; and supervisory guidance and moral suasion. In addition, participants were asked to consider using monetary policy tools for financial stability purposes. This paper presents the hypothetical macro-financial scenario, the set of macroprudential tools, and their transmission mechanism, as well as an account of the participants' assessment of vulnerabilities and potential policy actions under the scenario. The tabletop exercise abstracted from governance issues within the Federal Reserve System, focusing instead on economic mechanisms of alternative tools.
Keywords: G18; E58; G01; 330; macroprudential policy; monetary policy; tabletop exercise